2018
DOI: 10.1101/375717
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The flower pot method of REM sleep deprivation causes apoptotic cell death in the hepatocytes of rat

Abstract: Short running title: REM sleep deprivation causes liver cell death. Highlights of the study• We observed significant apoptosis in the hepatocytes of REMSD group of rats.• Our expression analysis confirmed altered expression for genes p53, Bcl2, Bax, and Caspase-3 after REMSD.• Protein level analysis supported our gene expression results for p53, Bcl2, Bax, Caspase 3 and Caspase 9 after REMSD.• Sleep recovery improved the respective genes and protein expression levels towards normalcy, signifying the functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
2

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…Previous studies had shown that NO exerts a protective effect by blocking TNF-α induced apoptosis and hepatotoxicity both in vivo and in vitro , by inhibiting the caspase-3-like protease activity 43 . Our unpublished results also show that REMSD can cause apoptosis in hepatocytes 36 . It suggests that might be excess of NO is being produced to counteract the oxidative stress generated due to sleep loss and it protects the hepatocytes from apoptotic death.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Previous studies had shown that NO exerts a protective effect by blocking TNF-α induced apoptosis and hepatotoxicity both in vivo and in vitro , by inhibiting the caspase-3-like protease activity 43 . Our unpublished results also show that REMSD can cause apoptosis in hepatocytes 36 . It suggests that might be excess of NO is being produced to counteract the oxidative stress generated due to sleep loss and it protects the hepatocytes from apoptotic death.…”
Section: Discussionsupporting
confidence: 59%
“…We used LPC group of rats as a reference group for statistical comparisons as CC and LPC groups had no significant differences in observed parameters. Our findings suggest that REM sleep deprivation of rats can increase ROS production in their hepatocytes which ultimately can induce apoptotic cell death 36 . Treatment of hepatocytes with H 2 O 2 or Xanthine/Xanthine oxidase can selectively induce production of ROS inside the hepatocytes and it can be quenched by Catalase or Oxypurinol treatment.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In the brain, REM sleep is involved in the reorganization of hippocampal excitability, pruning and maintenance of new synapses during development, and learning and memory consolidation [ 40 , 41 , 42 ]. Some recent studies also suggest that lack of REM sleep may cause cell death of somatic cells and neurons [ 43 , 44 , 45 ]. Outside of the brain, deprivation of the REM sleep was found to be associated with acute phase response in the liver, increased synthesis of pro-inflammatory cytokines such as IL1β, IL-6, and IL-12, and an increase in liver enzymes, alanine transaminase and aspartic transaminase [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we compared the effect of prolonged REM sleep loss in the brain and liver in order to compare and contrast the effects that occur simultaneously on these vital organs, as previous studies have indicated that REM sleep may have drastic effects on the liver [ 44 , 46 , 48 ]. To address this, we used a microarray technique to compare gene expression and identify the processes affected in the brain and liver of a given subject after REM sleep deprivation for nine days.…”
Section: Introductionmentioning
confidence: 99%